Feasibility and efficacy of an attachment-based intervention in a maltreatment sample in residential care: A pilot study. (October 2017) - Casonato, Marta; Nazzari, Sarah; Frigerio, Alessandra
The effects of the Video-feedback Intervention to promote Positive Parenting and Sensitive Discipline on improving maternal sensitivity and sensitive discipline were investigated using a randomized control design in a pilot sample of mothers at high risk of maltreatment. The study included 12 mothers and their 10- to 36-month-old children placed in parental residential care, due to a guardianship order issued by the Youth Court. Both at pretest and post-test, maternal sensitivity and sensitive discipline were assessed during mother–child interaction via observational measures. Mothers who received the intervention showed a significant reduction in dysfunctional strategies of maternal discipline. Results highlight the usefulness and feasibility of a brief residential care–based intervention in such a risk sample, with promising implications for the prevention of child maltreatment.